Proposal of an Automated Schema to Generate a Complex Password by Employing the Genetic Algorithm - Mohammed, Sura Jasim; Al-Murieb, Safa Saad (Science and Technology - Recent Updates and Future Prospects Vol. 8, 2024)
Due to the occurred increasing in information sharing, internet popularization, E-commerce transactions, and data transferring, security and authenticity become an important and necessary subject. During recent years and yet now the terms of security, data integrity, authenticity are very concern, whereas in order to authenticate users of any service that is worked online, the authentication of password is used. In this paper an automated schema was proposed to generate a strong and complex password which is based on entering initial data such as text (meaningful and simple information or not), with the concept of encoding it, then employing the Genetic Algorithm by using its operations crossover and mutation to generated different data from the entered one. The generated password is non-guessable and can be used in many and different applications and internet services like social networks, secured system, distributed systems, and online services. The proposed password generator achieved diffusion, randomness, and confusions, which are very necessary, required and targeted in the resulted password, in addition to the notice that the length of the generated password differs from the length of initial data, and any simple changing and modification in the initial data produces more and clear modification in the generated password. The generated password cannot be remembered, so that the application of such password is as a master password, which is saved in a file after it was generated and it is used in user specific configuration data for access the server, also it can be distributed among the users who share information and data, it can also be used for barcode generation for commercial field. The proposed work was done using visual basic programing language.